Genome-wide gene responses in a transgenic rice line carrying the maize resistance gene Rxo1 to the rice bacterial streak pathogen Xanthomonas oryzae pv. oryzicola - Zhou, Yongli; Xu, Mei-Rong; Zhao, Ming-Fu; Xie, Xue-Wen; Zhu, Ling-Hua; Fu, Binying; Li, Zhikang (Springer, 2010)
Non-host resistance in rice to its bacterial pathogen, Xanthomonas oryzae pv. oryzicola (Xoc), mediated by a maize NBS-LRR type R gene, Rxo1 shows a typical hypersensitive reaction (HR) phenotype, but the molecular mechanism(s) underlying this type of non-host resistance remain largely unknown.A microarray experiment was performed to reveal the molecular mechanisms underlying HR of rice to Xoc mediated by Rxo1 using a pair of transgenic and non-transgenic rice lines. Our results indicated that Rxo1 appeared to function in the very early step of the interaction between rice and Xoc, and could specifically activate large numbers of genes involved in signaling pathways leading to HR and some basal defensive pathways such as SA and ET pathways. In the former case, Rxo1 appeared to differ from the typical host R genes in that it could lead to HR without activating NDR1. In the latter cases, Rxo1 was able to induce a unique group of WRKY TF genes and a large set of genes encoding PPR and RRM proteins that share the same G-box in their promoter regions with possible functions in post-transcriptional regulation.In conclusion, Rxo1, like most host R genes, was able to trigger HR against Xoc in the heterologous rice plants by activating multiple defensive pathways related to HR, providing useful information on the evolution of plant resistance genes. Maize non-host resistance gene Rxo1 could trigger the pathogen-specific HR in heterologous rice, and ultimately leading to a localized programmed cell death which exhibits the characteristics consistent with those mediated by host resistance genes, but a number of genes encoding pentatricopeptide repeat and RNA recognition motif protein were found specifically up-regulated in the Rxo1 mediated disease resistance. These results add to our understanding the evolution of plant resistance genes.